2012
DOI: 10.1093/ntr/nts113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cigarette Smoke Exposure and Its Cessation on Body Weight, Food Intake and Circulating Leptin, and Ghrelin Levels in the Rat

Abstract: Circulating leptin could not explain by its own BW and FIR changes during the first few week of CSE in rats, in contrast to the rest of the CSE period as well as after its cessation. Serum ghrelin levels did not justify BW and FIR changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 43 publications
2
11
0
2
Order By: Relevance
“…1) and other metabolic and endocrine effects. Some of the mechanisms by which nicotine causes weight loss include: direct stimulation of melanocortin receptor 4 (MC4-R), which results in reduced food consumption 28 and serum levels of leptin 29,30 ; increased stimulation of the sympathetic nervous system, which results in increased levels of adrenaline and noradrenaline 31 (FIG. 1); lipolysis 32 (FIG.…”
Section: Nicotine-mediated Weight Lossmentioning
confidence: 99%
“…1) and other metabolic and endocrine effects. Some of the mechanisms by which nicotine causes weight loss include: direct stimulation of melanocortin receptor 4 (MC4-R), which results in reduced food consumption 28 and serum levels of leptin 29,30 ; increased stimulation of the sympathetic nervous system, which results in increased levels of adrenaline and noradrenaline 31 (FIG. 1); lipolysis 32 (FIG.…”
Section: Nicotine-mediated Weight Lossmentioning
confidence: 99%
“…The experimental animals were exposed to the cigarette smoke in the chamber, a glass box in a cube shape (aquarium shape) with the size of 30 × 40 × 80 cm for keeping the rats and a hood over the aquariumshaped box to evacuate the extra smoke from the environment ( Figure 1) described by Ypsilantis et al 2012. 15 Animals were daily exposed to cigarette smoke (2-3 cigarettes) for total duration of 30 min (with intermittent exposure to fresh air for 2 min after every 10 min of smoke exposure). At the end of each week of exposue, the changes in the behavior were studied by using the forced swim test and elevated plus maze.…”
Section: Experimental Designmentioning
confidence: 99%
“…Ypsilantis et al [30] found in a preclinical study with male wistar rats that plasma levels of total ghrelin did not change during 8 weeks of cigarette smoking exposure and in the first 7 weeks after smoking cessation. By contrast, Tomoda et al [31] could show that the plasma levels of acetylated ghrelin were significantly higher in a group of 10 wistar rats after cigarette smoke exposure (30 cigarettes twice a day for 5 days a week for four weeks) compared to control animals without cigarette smoke exposure.…”
Section: Discussionmentioning
confidence: 99%
“…One research group was able to find high ghrelin plasma levels to predict the risk of relapse in abstinent smokers [29]. Even the evidence from animal models is conflicting with studies showing both no effect [30] and an upregulation of ghrelin plasma levels by exposure to cigarette smoke [31]. …”
Section: Introductionmentioning
confidence: 99%